UN MODELO DE ANÁLISIS PARA DIAGNÓSTICO DE EMPRESAS PYMES FAMILIARES - Radano, Eduardo; Velinsone, Daniel (European Scientific Journal, ESJ, 2015)
Both the owners of a company and the consultants who are invited to work in it, are very important in determining the present situation of the company at a given point in time. Models, approaches, and experiences are numerous. It was provided by each profession and the particular experience and expertise of each professional. We found it interesting to provide two inputs that provides a wealth of information through their extensive applications on time and to very large organizations.